IMAGINED ISLAMIC SOCIETIES AND THE ROLE OF ULEMA IN CONTEMPORARY INDONESIA - Mahfud, Choirul (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
Abstract This article focuses discuss questions about how the role and contribution of ulema in the social life of religion in Indonesia. Also, how is the typology and characteristic of ulema in contemporary Indonesia. Sociologically, ulema is part of the most important topics in the study of religious institutions in the Islamic world, including when speaking about Islam in Indonesia. Ulema is also juxtaposed with umara. In this case, the position and role of the ulema are like an "informal" leader in a nation for Muslim Societies. In Indonesia, ulema has a central role in religious and state life to shape the imagined Islamic societies, such as Nusantara Islam and others. From time to time, ulema has made major contributions from before until after independence to the present. This is evident from the historical track record of ulema institutions in Indonesia. From Sabang to Merauke island, the term of ulema has an interesting nickname. For example, there are many other names of ulama like Kiai (Java), Tengku (Aceh), Ajengan (Sundanese), Buya (Minangkabau), Sheikh (North Sumatra), Tuan Guru (Lombok, West Nusa Tenggara and Kalimantan). Keywords: Ulema, Indonesian Islam, and Imagined Islamic Societies